Linking Fish to Food and Nutrition Security: Swot Analysis of Traditional Fish Processing in Nigeria - Fakoya, K. A.; Akintola, S. L. (Fishery Technology, 2019)
Globally, there is a growing awareness on the role of fish in the food and nutritional security discourse. In sub-Saharan Africa, post-harvest losses occur predominantly in small-scale fisheries, thus limiting to role of fish in enhancing food security. Women dominate traditional fish processing and are key to reducing post-harvest losses thus deepening availability, affordability and choice of fish products for consumers. However, post-harvest practices are characterized by low efficiencies that undermine efforts to reduce production losses. Therefore, predicated on the need to prioritize a paradigm shift to sustainable supply of safe and improved fish quality in domestic markets, a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis was conducted to give a ‘snapshot’ of traditional fish smoking. Findings provided information on the current state of affairs, highlighting the constraints and possible strategies to enhance the role of processed fish in food security and improve livelihood. Based on these, policies and interventions were recommended to re-position traditional fish processing practices with consideration for gender equitable participation.